Efeitos de um protocolo de fortalecimento da musculatura do assoalho pélvico em grupo para mulheres com perda urinária - Correia, Grasiéla Nascimento (Universidade Federal de São Carlos, 2010)
The purpose of this study was to evaluate the effects of a kinesiotherapy protocol in a group-based for strengthen the pelvic floor muscles (KGSPF) for the pelvic floor muscle (PFM) function and pressure level, quality of life (QOL) and isometric and isokinetic hip adductors peak torque (PT) among women with urinary incontinence (UI) that was not sedentary. Fifteen women (mean age 60,20 ± 8,16) were enrolled in this study. They were evaluated, at beginning and after 12 weeks, by a clinical evaluation; one hour pad test; three-day voiding diary; a QOL with King Health Questionnaire (KHQ); PFM function (digital and perioneometer) and isometric and isokinetic hip adductors PT. The KGSPF protocol consisted of 12 sessions of one hour, once a week. The KGSPF protocol included exercises to strengthen PFM, information and guidance for UI. The data were analyzed by non-parametric Wilcoxon test and Spearman coefficient correlation. The significance level was 5%. After 12 weeks, the group presented a significant improvement of QOL and PFM function and pressure. It was presented a significant decrease for isometric hip adductors PT, one hour pad test (p=0,03), urgency episodes (p=0,04), and UI (p=0,02). It was found moderate negative correlation between age and the isokinetic hip adductors PT for dominant side (r= -0,53; p=0,04) and non-dominant side (r= -0,57; p=0,03); between the PFM contraction pressure and isokinetic hip adductors PT for dominant side (r= -0,62; p=0,03) and nondominant side (r= -0,64;p= 0,02); and between contraction force of PFM fast fibers and isometric hip adductors PT for dominant side (r= 0,60; p=0,03) and non-dominant side (r=-0,59; p=0,04). In conclusion, the KGSPF protocol was effective to decrease UI and isometric hip adductors PT, and to improve QOL.
Keywords: Fisioterapia; Saúde da mulher; Incontinência urinária; Assoalho pélvico; Reabilitação; Terapia de grupo; Urinary incontinence; Pelvic floor; Torque; Group therapy; Physiotherapy; Pelvic floor muscle training; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL